Kekaisaran Utsmani hingga Era Erdoğan: Jejak Perubahan Identitas Islam dalam Sejarah Turki: The Ottoman Empire to the Erdoğan Era: Traces of Change in Islamic Identity in Turkish History - Andi Wawan Mulyawan; Abd. Rahim Yunus; Susmihara, Susmihara (Litera Academica Publishing, 2025)
This study aims to examine the historical and ideological transformation of Turkey, from the Ottoman Empire as a symbol of Islamic glory to the Republic of Turkey founded on secular principles. The study covers the origins and development of the Ottoman Empire, the internal and external factors leading to its collapse, the ideas and reforms of Mustafa Kemal Atatürk, the forms of secularization implemented in state life, the resilience of Islamic values amid the tide of secularism, the impact of secularization on Turkish society, and the contemporary dynamics between secularism and the resurgence of Islamism. This research employs a descriptive qualitative method with historical and analytical approaches. The historical approach traces the journey of the Ottoman Empire until its fall and the establishment of the modern Turkish Republic, while the analytical approach is used to assess secularization policies and their impacts on society. The findings reveal that Turkey has undergone major transformations in its political, social, and cultural systems. Although secularism has been thoroughly applied, Islamic identity has persisted and continues to flourish within society. The process of secularization has succeeded in driving rapid modernization, yet it has also generated tensions between the state and religious groups. In the contemporary context, Turkey serves as a battleground between Atatürk’s legacy of secularism and the growing aspirations of Islamism expressed through democratic means.